![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, (9.x-21) : 3 = 2
=>9x-21=6
=>9x=27
=>x=3
b, (x-39)-21=0
=>x-39-21=0
=>x-60=0
=>x=60
c, 231+(312-x)=531
=>231+312-x=531
=>543-x=531
=>x=543-531
=>x=12
d, 53.(9-x)=53
=>9-x=1
=>x=8
a/ \(\frac{\left(9x-21\right)}{3}=2\)
\(\Rightarrow9x-21=2\cdot3=6\)
\(\Rightarrow9x=6+21=27\)
\(\Rightarrow x=\frac{27}{9}=3\)
b/ \(\left(x-39\right)-21=0\)
\(\Rightarrow x-39=0+21=21\)
\(\Rightarrow x=21+39=60\)
c/ \(231+\left(312-x\right)=531\)
\(\Rightarrow312-x=531-231=300\)
\(\Rightarrow x=312-300=12\)
d/ \(53\cdot\left(9-x\right)=53\)
\(\Rightarrow9-x=\frac{53}{53}=1\)
\(\Rightarrow x=9-1=8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3x = 32 . 9
3x = 32 . 32
3x = 34
=> x = 4
b) ( 21 + x ) : 9 = 95 : 94
(21 + x ) : 9 = 9
21 + x = 9 . 9
21 + x = 81
x = 81 - 21
x = 60
c) 5x + 1 - 13 = 613
5x = 613 + 13 - 1
5x = 625
5x = 54
=> x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
=> ( 6 - 9 ) x | x - 3 | =-21
=> - 3 x | x - 3 | = -21
=> | x - 3 | = -21 : -3 = 7
=> x - 3 = 7 hoặc x - 3 = -7
với x- 3 = 7 => x = 7+3=10
với x - 3 = -7 => x = -7 + 3 =-4
\(\Rightarrow\left|x-3\right|\times\left(6-9\right)=-21\)
\(\Rightarrow\left|x-3\right|\times\left(-3\right)=-21\)
\(\Rightarrow\left|x-3\right|=-21\div\left(-3\right)\)
\(\Rightarrow\left|x-3\right|=7\)
\(\Rightarrow\orbr{\begin{cases}x-3=7\\x-3=-7\end{cases}\Rightarrow\orbr{\begin{cases}x=10\\x=-4\end{cases}}}\)
KL \(\orbr{\begin{cases}x=10\\x=-4\end{cases}}\)Để 6| x - 3 | - 9| x - 3 |=-21
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
6|x - 3| - 9|x - 3| = 21
(6 - 9)|x - 3| = 21
- 3|x - 3| = 21
=> |x - 3| = - 7
Vì |x - 3| ≥ 0 mà - 7 < 0
=> x = rỗng
6|x-3|- 9|x-3|=21
(6-9).|x-3|=21
(-3).|x-3|=21
|x-3|=21:(-3)
|x-3|=-7
|x-3| >hoặc = 0
=> |x-3|=-7 là điều vô lí
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2 . x + 12 = 36
2 . x = 36 - 12
2 . x = 24
x = 24 : 2
x = 12
Vậy x = 12
b) (x + 21) : 8 + 12 = 21
( x + 21 ) : 8 = 21 - 12
( x + 21 ) : 8 = 9
x + 21 = 9 . 8
x + 21 = 72
x = 72 - 21
x = 51
Vậy x = 51
c) (3 . x - 18) . (x - 9) = 0
\(\Rightarrow\begin{cases}3.x-18=0\\x-9=0\end{cases}\)
\(\Rightarrow\begin{cases}3.x=18\\x=0+9\end{cases}\)
\(\Rightarrow\begin{cases}x=18:3=6\\x=9\end{cases}\)
Vậy \(x\in\left\{6;9\right\}\)
a)
\(2x+12=36\)
\(\Rightarrow2\left(x+6\right)=36\)
\(\Rightarrow x+6=18\)
=> x = 12
Vậy x = 12
b)
\(\left(x+21\right):8+12=21\)
\(\Rightarrow\left(x+21\right):8=9\)
\(\Rightarrow x+21=72\)
=> x = 51
Vậy x = 51
c)
\(\left(3x-18\right)\left(x-9\right)=0\)
\(\Rightarrow3\left(x-6\right)\left(x-9\right)=0\)
\(\Rightarrow\left(x-6\right)\left(x-9\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}x-6=0\\x-9=0\end{array}\right.\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=6\\x=9\end{array}\right.\)
Vậy x = 6 ; x = 9
3x + 9 = -21
3x = ( -21 ) - 9 = -30
x = ( -30 ) : 3 = -10
3.x= -21-9
3.x=-30
x=-30:3
x=10
vậy x=10